Magnetic structure and properties of centrosymmetric twisted-melilite K2CoP2O7. Issue 19 (3rd May 2017) - Sale, Matthew; Avdeev, Maxim; Mohamed, Zakiah; Ling, Chris D.; Barpanda, Prabeer
Abstract : The magnetic structure and properties of K2 CoP2 O7 were studied by magnetometry and neutron powder diffraction. Below 11 K the material adopts a G-type antiferromagnetic structure in contrast to the melilite-type Sr2 CoGe2 O7 which orders in a C-type. Ab initio DFT calculations were performed to understand this difference. Abstract : Twisted-melilite dipotassium cobalt pyrophosphate (K2 CoP2 O7, P 42 / mnm, #136), originally reported by Gabelica-Robert (1981), was synthesized in powder form by a standard solid-state reaction route. The magnetic properties of the material were studied by magnetometry and its magnetic structure determined using neutron powder diffraction for the first time. Below T N = 11 K, the material adopts a G-type antiferromagnetic structure with moments aligned in the ab -plane (magnetic space group Pn ′ nm, #58.3.473). Ab initio calculations were performed to examine the isotropic magnetic spin exchange parameters as well as the preferred direction of magnetic moments due to spin–orbit coupling. The relationship between crystal structure geometry and the strength of the magnetic interactions was examined and compared to those of melilite-type Sr2 CoGe2 O7 .